2018
DOI: 10.1111/medu.13745
|View full text |Cite
|
Sign up to set email alerts
|

Education or regulation? Exploring our underlying conceptualisations of remediation for practising physicians

Abstract: Context The remediation of practising physicians is coming to the fore in several countries in response to increasing demands for physician accountability and quality improvement initiatives in health care. However, the profession continues to grapple with the concepts and processes of remediation, particularly for physicians in practice who struggle with performance issues related to clinical competence. This suggests that current conceptualisations of remediation might be contributing to this situation. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
35
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(35 citation statements)
references
References 23 publications
(23 reference statements)
0
35
0
Order By: Relevance
“…Remediation has been classified as a ‘wicked’ problem with which the medical profession has struggled for decades . One of the reasons for this refers to the fact that remediation has tended to be conceptualised as an educational issue; however, few studies are underpinned by educational theory . Recent work by Prescott‐Clements et al has shown how conceptualisations have moved towards the use of behavioural change theories to underpin remediation models.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Remediation has been classified as a ‘wicked’ problem with which the medical profession has struggled for decades . One of the reasons for this refers to the fact that remediation has tended to be conceptualised as an educational issue; however, few studies are underpinned by educational theory . Recent work by Prescott‐Clements et al has shown how conceptualisations have moved towards the use of behavioural change theories to underpin remediation models.…”
Section: Introductionmentioning
confidence: 99%
“…Recent work by Prescott‐Clements et al has shown how conceptualisations have moved towards the use of behavioural change theories to underpin remediation models. We conceptualised remediation as a behaviour change intervention because a large part of professionalism relates to behaviours …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Opining that challenges with physician remediation are in part due to our limited understanding of how remediation of practising physicians is conceptualised, Bourgeois‐Law et al conducted a qualitative study exploring the conceptualisation of the remediation of practising physicians. In an article featured in this issue, the authors identify two conceptualisations of remediating practising physicians: remediation as an educational process on a continuum of learning and remediation as a regulatory process . They seem to suggest that simultaneously holding these ‘conflicting’ conceptualisations of physician remediation is somehow problematic, and conclude that efforts need to be made to avoid the ‘de‐professionalisation’ that accompanies the regulatory conceptualisation of remediation.…”
mentioning
confidence: 99%
“…Stigmatisation, loss of autonomy and the resulting sense of ‘de‐professionalisation’ are well‐founded concerns raised in relation to physician remediation . A systemic approach to remediation has been recommended as one way of addressing the challenges that are part of implementing physician remediation .…”
mentioning
confidence: 99%